2009
DOI: 10.2746/042516409x360208
|View full text |Cite
|
Sign up to set email alerts
|

Blood culture status in mature horses with diarrhoea: A possible association with survival

Abstract: Results of blood cultures may be useful in formulating a prognosis for horses with diarrhoea. Further research is required to determine the effect of antimicrobial treatment on outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 25 publications
1
39
3
Order By: Relevance
“…The potential for bacterial translocation from the gastrointestinal tract during exercise has also been proposed . Gram‐positive cocci, consistent with the synovial isolates from the present study, were occasionally identified in a study of bacteraemia in horses with diarrhoea . Other commensal organisms of the gastrointestinal tract have been isolated in synovial sepsis of suspected haematogenous origin .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The potential for bacterial translocation from the gastrointestinal tract during exercise has also been proposed . Gram‐positive cocci, consistent with the synovial isolates from the present study, were occasionally identified in a study of bacteraemia in horses with diarrhoea . Other commensal organisms of the gastrointestinal tract have been isolated in synovial sepsis of suspected haematogenous origin .…”
Section: Discussionsupporting
confidence: 81%
“…The gastrointestinal tract has also been proposed as an origin of bacteraemia in cases of haematogenous synovial sepsis . Bacteraemia has been associated with intestinal disease in the adult horse including enterocolitis and small intestinal lesions requiring resection . However, severe gastrointestinal disease was not identified in the present study.…”
Section: Discussioncontrasting
confidence: 65%
“…Their use is advocated by some authors when there is a high risk of bacterial translocation and bacteraemia because of severe gastrointestinal inflammation or neutropenia. A significant proportion (29 per cent) of adult horses with diarrhoea were bacteraemic in one study, but the administration of antimicrobials did not affect survival or duration of disease (Johns and others 2009). However, antimicrobials are also associated with the development of diarrhoea (Weese and others 2006).…”
Section: Clostridial Enterocolitismentioning
confidence: 98%
“…29 Studies have shown the presence of bacteremia in some horses with colitis; however, a similar investigation into horses with colic is warranted. 30 Previous treatment with antimicrobials does not affect the incidence of bacteremia. 30 Likewise, the presence of bacteremia does not necessarily mean that antimicrobials will reduce later complications associated with infections.…”
Section: Section 3: Antimicrobial Use In the Field For Horses And Foamentioning
confidence: 99%
“…30 Previous treatment with antimicrobials does not affect the incidence of bacteremia. 30 Likewise, the presence of bacteremia does not necessarily mean that antimicrobials will reduce later complications associated with infections.…”
Section: Section 3: Antimicrobial Use In the Field For Horses And Foamentioning
confidence: 99%